Multisectoral Challenges in The Implementation of Land Redistribution: Legal, Social, And Administrative Perspectives - Novianti, Leny (Jurnal Ilmiah Teunuleh, 2024)
Land redistribution is the main pillar of agrarian reform policy that aims to create justice in land tenure and utilization. However, its implementation in Indonesia is still faced with various interrelated multi-sectoral challenges, especially in legal, social, and administrative aspects. This study aims to critically analyze the complexity of land redistribution implementation from these three perspectives using a descriptive qualitative approach and literature study. The results show that overlapping regulations, weak legal certainty, and conflicts between regulations are the main obstacles from the legal side. Socially, low agrarian literacy, lack of public participation, and resistance from capital owner groups weaken the legitimacy of the program. On the administrative side, weaknesses in the data collection system, limited human resources, and poor coordination between institutions are significant implementation obstacles. This research emphasizes the need to reformulate the land redistribution policy with an intersectoral, participatory, and social justice-based approach. Recommendations are made to strengthen synergies between stakeholders, harmonize regulations, and increase institutional and community capacity in supporting inclusive and sustainable agrarian reform.